Evaluation of surface modification of smokeless powder grain by ballistic efficiency parameter - Velehradský, Ladislav; Prchal, Pavel (Univerzita Pardubice, 2007)
The electron densities in a selected set of explosives with composition C-H-N-O were calculated (i) for individual molecules and (ii) for molecules placed in crystal cell. Indirect linearity between difference of absolute partial charges for bonds C-NO2, N-NO2 and O-NO2 versus the bond lenghts was found in both cases. The influence of non-covalent hydrogen bonds causing distinctly decreasing impact senstitivity was confirmed. Possibilities of sensitivity prediction of new energetic materials are discussed on the basic of the results obtained from impact sensitivity (the values taken from literature) and from theoretical methods, such a molecular mechanics, and the electron density for a set of twenty explosives.
Keywords: výbušiny; hoření; bezdýmé prachy; detonační parametry